2011
DOI: 10.1063/1.3576910
|View full text |Cite
|
Sign up to set email alerts
|

Compact tunable sub-terahertz oscillators based on Josephson junctions

Abstract: Essential applications of terahertz technology are urgently in need of compact, tunable solid-state continuous wave radiation sources. However, no satisfactory solution is yet available for the frequency range of up to approximately 1.0 THz. Here, we present coherent radiation from large series arrays of Josephson junctions between 0.1 and 0.25 THz with off-chip radiation power of 7 μW. Niobium junctions oscillate at 4.2 K and the detection has been done at room temperature. The well-known obstacle to impedanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 17 publications
(15 reference statements)
1
4
0
Order By: Relevance
“…It should be noticed that we did not observe on IV curves any fine details making evident coupling to dielectric cavity formed by dielectric silicon substrate as it has been reported by us earlier [4]. Nevertheless, the substrate can act as an additional resonator but its role in the synchronization effectiveness of the series JJ array will have to be revealed in future.…”
Section: Layout Of the Jj Arrayssupporting
confidence: 40%
See 2 more Smart Citations
“…It should be noticed that we did not observe on IV curves any fine details making evident coupling to dielectric cavity formed by dielectric silicon substrate as it has been reported by us earlier [4]. Nevertheless, the substrate can act as an additional resonator but its role in the synchronization effectiveness of the series JJ array will have to be revealed in future.…”
Section: Layout Of the Jj Arrayssupporting
confidence: 40%
“…The layouts of two samples investigated here are presented schematically in figure 1. The first series array is similar to those described previously [4]. It consists of seven subarrays.…”
Section: Layout Of the Jj Arraysmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17] It might be possible to make 1 mW level of power emission even by making an array of conventional Josephson junctions, if the number of 10 4 -10 5 of identical Josephson junctions were made to be synchronized. [18][19][20][21][22] This is technically formidable, hindering high power generation using conventional Josephson junctions. Furthermore, the superconducting gap 2D is only a few mV, so that it cannot, in principle, go beyond $1 THz in conventional Josephson junctions.…”
mentioning
confidence: 99%
“…The emission was found to be coherent, strong, and continuous. Because Bi2212 crystals are comprised of many equivalent intrinsic Josephson junctions (IJJs) naturally stacked along the c-axis direction [9], such a large number of IJJs may work coherently to emit the THz radiation as for a large planar array fabricated by low-T c superconductors [10][11][12][13][14]. Further detailed spectroscopic studies have revealed that the emission frequency f follows the ac-Josephson relation [15] = f ev h 2…”
Section: Introductionmentioning
confidence: 99%